Effect of the VO2 time-averaging interval on the reproducibility of VO2max in healthy athletic subjects - Midgley, A. W.; McNaughton, L. R.; Carroll, S. (Clinical Physiology and Functional Imaging, 2007)
Aims: Limited research has investigated the most appropriate oxygen uptake (VO2) data averaging method to obtain reliable and valid maximal oxygen uptake (V2max) values. This study investigated the effect of the VO2 time-averaging interval on the reproducibility of VO2max.